2021
DOI: 10.1111/jcmm.16750
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of N6‐methyladenosine modification of circRNAs in glioblastoma

Abstract: This research systematically profiled the global N6‐methyladenosine modification pattern of circular RNAs (circRNAs) in glioblastoma (GBM). Based on RNA methylation sequencing (MeRIP sequencing or N6‐methyladenosine sequencing) and RNA sequencing, we described the N6‐methyladenosine modification status and gene expression of circRNAs in GBM and normal brain tissues. N6‐methyladenosine–related circRNAs were immunoprecipitated and validated by real‐time quantitative PCR. Bioinformatics analysis and related scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…As shown in Figure 1E , when we counted the number of m7G peaks for each mRNA in the two groups, we found that most methylated mRNAs in HL60 and HL60/MX2 cells had only one m7G peak (70.8% and 74.3%, respectively). In the two groups, approximately 20% of the genes recorded two m7G peaks, and less than 10% of the genes contained more than three m7G peaks, which was consistent with previous studies of methylation in other diseases ( 22 , 23 ). We performed a statistical analysis of the length of the methylation peak, and our results revealed that there was no statistically significant difference between the two groups.…”
Section: Resultssupporting
confidence: 92%
“…As shown in Figure 1E , when we counted the number of m7G peaks for each mRNA in the two groups, we found that most methylated mRNAs in HL60 and HL60/MX2 cells had only one m7G peak (70.8% and 74.3%, respectively). In the two groups, approximately 20% of the genes recorded two m7G peaks, and less than 10% of the genes contained more than three m7G peaks, which was consistent with previous studies of methylation in other diseases ( 22 , 23 ). We performed a statistical analysis of the length of the methylation peak, and our results revealed that there was no statistically significant difference between the two groups.…”
Section: Resultssupporting
confidence: 92%
“…Although surgical techniques and radiochemotherapy regimens have been improving in recent decades, the survival rate of glioma has not increased as expected [ 29 32 ]. Chemoresistance is a major cause of chemotherapy failure in glioma patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, mRNA modi cation, especially m6A, has drawn lots of attention. m6A has been indicated involving in various biological processes, such as cell proliferation, invasion, metastasis, immune system evasion, stress response, tumorigenesis, and so on [36][37][38][39][40][41][42][43][44]. m5C, as a new modi cation factor, also is related to tumor translation, occurrence and metastasis.…”
Section: Discussionmentioning
confidence: 99%